Rosai-Dorfman disease presenting with extensive cutaneous manifestation - Case report Doença de Rosai-Dorfman com manifestação cutânea extensa - Relato de caso - Paula Azevedo Borges Leal; Adrilena Lopes Adriano; Marcelle Parente Breckenfeld; Igor Santos Costa; Antônio Renê Diógenes de Sousa; Heitor de Sá Gonçalves (Sociedade Brasileira de Dermatologia, 2013)
Rosai-Dorfman disease is a benign, self-limited, idiopathic proliferative histiocytic disorder. It was first described in 1969 by Rosai and Dorfman. In its typical form the disease is characterized by extensive cervical lymphadenopathy associated with fever, polyclonal gammopathy and leukocytosis with neutrophilia. The skin is the most common site affected. Extranodal manifestations have been reported in 43% of cases. In this study, we report an atypical case of Rosai-Dorfman disease in a female with massive cutaneous manifestation on the thigh, associated with a minimal lymphadenopathy limited to the regional inguinal lymph nodes. A doença de Rosai-Dorfman é uma desordem benigna, autolimitada, idiopática, decorrente da proliferação de histiócitos. Foi descrita pela primeira vez por Rosai e Dorfman em 1969. Tipicamente, a doença se caracteriza por extensa linfadenopatia cervical, febre, gamopatia monoclonal e leucocitose com neutrofilia. Manifestações extranodais são encontradas em 43% dos casos, sendo a pele o sítio extranodal mais comumente afetado. No trabalho, apresentamos um caso de doença de Rosai-Dorfman com apresentação cutânea exuberante na coxa direita e discreto comprometimento linfonodal limitado à cadeia regional.